Pelatihan Pembuatan Media Pembelajaran Inovatif Mahasiswa Calon Guru IPA - Sitti Rahma Yunus; Arie Arma Arsyad; St. Mutia Alfiyanti Muhiddin; Rifda Nur Hikmahwati Arif; Hardi Hamzah (JKM: Jurnal Kemitraan Masyarakat, 2023)
In order to improve the quality of students in welcoming the world of education in the era of society 5.0, the Lecturer Team held a service activity by conducting training in making innovative teaching media. The purpose of this service activity for students is to provide knowledge and skills to make innovative media that are useful in science learning. The problem faced is the lack of understanding of prospective science teacher students in finding ideas about innovative media that are useful today. This training was held with 56 students participating. The methods used were: lectures, discussions and sharing, as well as guidance on making innovative learning media. The results of the service activities are that students are able to make innovative learning media in the form of utilizing applications and media products.